Pengaruh Kesadaran, Penegakan Hukum dan Kepercayaan Terhadap Kepatuhan Wajib Pajak di KPP Pratama Batam Utara - Puspitaningtyas, Indrianti; Purba, Mortigor Afrizal (Universitas 17 Agustus 1945 Jakarta, 2025)
This research aims to analyze the effect of taxpayer awareness, law enforcement, and trust in tax authorities on individual taxpayer compliance in the working area of KPP Pratama Batam Utara. The main problem is the low level of tax reporting and payment, even though the number of registered taxpayers increases each year. During 2020–2024, the average tax reporting rate remained below 21%, with a significant gap between those who report and those who pay. This study uses a quantitative method with a descriptive approach and multiple linear regression analysis. Data were collected using questionnaires from individual taxpayers registered in 2024. The results show that taxpayer awareness, law enforcement, and trust in tax authorities have a simultaneous and partial effect on compliance. Taxpayer awareness has the most dominant influence. Therefore, tax policy strategies must focus on continuous education, improving service quality, and transparency in tax management to increase voluntary taxpayer participation.